The Role of the State Administrative Court as a Control Mechanism Over Government Administration - Akuna, Sandrawati (Universitas Negeri Gorontalo, 2025)
The State Administrative Court (PTUN) plays a central role in upholding the rule of law and good governance by providing oversight of government administration. PTUN serves as a judicial institution authorized to resolve disputes between citizens or private legal entities and state administrative bodies or officials concerning state administrative decisions (KTUN). This study aims to analyze the role of PTUN in protecting citizens' rights and enforcing the principles of good governance. The research employs a normative juridical method with a statutory and conceptual approach. The findings indicate that although PTUN holds absolute competence in resolving administrative disputes, the effectiveness of its rulings still faces challenges, including government non-compliance with court decisions. Additionally, the enactment of Law No. 30 of 2014 on Government Administration has expanded PTUN’s authority, particularly in assessing the presence of abuse of power by state administrative officials. However, the implementation of this regulation still requires strengthening in terms of transparency and accountability. Therefore, enhancing PTUN’s institutional capacity is necessary to ensure legal certainty and justice for the public. In conclusion, PTUN plays a strategic role in maintaining the balance between governmental power and the protection of citizens’ rights, thereby fostering a more transparent, accountable, and just administrative system